Challenges and Adaptation Strategies of Students with Disabilities in Higher Education in Bangladesh - Md. Ashraful Alam; Imrul Kabir (Camarines Sur Polytechnic Colleges, 2023)
Education is a fundamental human right to which every human should have access. However, in Bangladesh, people with disabilities continue to be denied access to education in a variety of ways; even with the widespread expansion of higher education, they have limited access to it. Also, those who have crossed various barriers and got admission to different higher education institutions face various challenges, including infrastructural barriers and other academic and administrative problems that affect their chances of growing up as average students. Considering this aspect, this article is intended to determine the challenges faced by students with disabilities and their adaptation strategies in higher education in Bangladesh. It applied a mixed-method approach in which quantitative and qualitative data were collected from four leading public universities in Bangladesh. The results indicate that students with disabilities still face a variety of challenges on their campuses. However, to overcome these challenges, they apply adaptive strategies such as using assistive devices, bilingual books, and the help of friends, which are not favorable enough for them to cope with the situation and continue their studies.